2018
DOI: 10.3390/jdb6030022
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the Etiology of Mammalian Neural Tube Closure Defects from Developmental, Genetic and Evolutionary Studies

Abstract: The human neural tube defects (NTD), anencephaly, spina bifida and craniorachischisis, originate from a failure of the embryonic neural tube to close. Human NTD are relatively common and both complex and heterogeneous in genetic origin, but the genetic variants and developmental mechanisms are largely unknown. Here we review the numerous studies, mainly in mice, of normal neural tube closure, the mechanisms of failure caused by specific gene mutations, and the evolution of the vertebrate cranial neural tube an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 223 publications
(405 reference statements)
1
50
0
Order By: Relevance
“…A critical step in the closure of the mouse midbrain is the transformation of the neural plate from convex to concave ( Figure 1A–C ; Nikolopoulou et al, 2017 ; Vijayraghavan and Davidson, 2017 ; Juriloff and Harris, 2018 ). Prior to closure, the cranial neural plate has an open, rams-horn shape ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A critical step in the closure of the mouse midbrain is the transformation of the neural plate from convex to concave ( Figure 1A–C ; Nikolopoulou et al, 2017 ; Vijayraghavan and Davidson, 2017 ; Juriloff and Harris, 2018 ). Prior to closure, the cranial neural plate has an open, rams-horn shape ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…During development, neuroepithelial cells undergo extensive remodeling to transform a flat sheet into a fully closed tube that gives rise to the brain and spinal cord of the animal. Distinct genetic circuits are required for neural tube closure in different regions along the head-to-tail axis, translating positional information into location-appropriate cell behaviors (Wilde et al, 2014;Aw and Devenport, 2017;Nikolopoulou et al, 2017;Juriloff and Harris, 2018). Although many studies have focused on mechanisms of neural tube closure in the spinal cord, one-third of human neural tube defects arise from a failure of closure in the cranial region, resulting in exencephaly-an inoperable and terminally lethal birth defect (Zaganjor et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Two potential hypotheses for this reduced proliferation are (a) an overall reduction in cellular metabolism due to C2 treatment impacting mitochondrial function, and (b) ciliary disruption due to C2 treatment disrupts cellular functionality and division. Ceramides are implicated in reducing the mitochondrial respiration of skeletal muscle cells, and several lines of study have indicated a potential role of primary cilium in the development of NTDs . Ceramides are reported to regulate the generation and elongation of primary cilium .…”
Section: Discussionmentioning
confidence: 99%
“…Ceramides are implicated in reducing the mitochondrial respiration of skeletal muscle cells, 71,72 and several lines of study have indicated a potential role of primary cilium in the development of NTDs. [73][74][75][76] Ceramides are reported to regulate the generation and elongation of primary cilium. 77,78 Future studies will examine cellular metabolism in the early embryo and explore the role of ceramides in regulating primary cilia during neural tube closure under high C2 conditions.…”
Section: Embryonic Defect Datamentioning
confidence: 99%
“…53 Interestingly, both lack of and excessive apoptosis have been associated with NTDs in animal models. Alterations in apoptotic genes Casp3 and Apaf1 impair closure at the midbrain and hindbrain; 54,55 however, excessive cell death has also been associated with failure of neural tube closure, highlighting the delicate balance that must be maintained during neurodevelopment. 27,56 Closure Sites in Primary Neurulation Primary neurulation in mammals is discontinuous with the three separate closure locations arising along the developing neural tube, which is in contrast to an older model that describes the neural tube closing in a continuous, zipper-like fashion ( Figure 2).…”
Section: Neural Plate Bendingmentioning
confidence: 99%